A novel structure of magnetic geared generator in dual-rotor wind turbine - Yousefnejad, Soheil; Heidary, Hossein; Cirimele, Vincenzo; Ro, Jong Suk (Institute of Advanced Engineering and Science, 2024)
Variable-speed constant-frequency generating systems are commonly employed in wind turbines to enhance efficiency and minimize losses. Additionally, the utilization of dual-rotor wind turbines enables the capture of a greater amount of wind energy, leading to a significant increase in efficiency. Traditionally, dual-rotor wind turbines are managed by a full-scale power converter, and the rotor current is transmitted through brushes, which substantially raises the system's cost. To address these challenges, this study introduces a novel configuration that enables power control with a smaller power converter. In contrast to conventional dual-rotor wind turbines that generate power using both rotors, the proposed structure designates one rotor as a system controller. Apart from these benefits, the proposed structure greatly enhances conversion performance by notably improving the power factor. A comparison with existing configurations described in literature is conducted to demonstrate the superiority of the proposed structure.